An Analysis of the Factors Influencing Non-Performing Loans at Perumda BPR Garut - Rahmanisa, Riska; Dewi Ungkari, Marti; Kartiko, Erik (Lafadz Jaya Publisher, 2025)
This research was organized under the title: